2021
DOI: 10.1186/s12985-021-01655-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and functional characterization of five novel Salmonella-targeting bacteriophages

Abstract: Background The host-unrestricted, non-typhoidal Salmonella enterica serovar Enteritidis (S. Enteritidis) and the serovar Typhimurium (S. Typhimurium) are major causative agents of food-borne gastroenteritis, and the host-restricted Salmonella enterica serovar Gallinarum (S. Gallinarum) is responsible for fowl typhoid. Increasing drug resistance in Salmonella contributes to the reduction of effective therapeutic and/or preventive options. Bacteriophages appear to be promising antibacterial tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…UPWr_S1, UPWr_S3, and UPWr_S4 phages are capable of infecting zoonotic pathogens such as S. Enteritidis as well as S. Gallinarum, which is the etiological factor of fowl typhoid. Regardless of their ability to infect various Salmonella serovars and lytic life cycle, they can be considered useful tools in the biological control of salmonellosis (Kuzmińska-Bajor et al, 2021). In this study, we found that UPWr_S1, UPWr_S3, and UPWr_S4 phages alone and the UPWr_S134 phage cocktail exhibited a great ability to decrease the number of Salmonella from biofilm structures in a 96-well microtiter plate and on stainless steel washers formed by strong and moderate biofilm producers, S. Enteritidis ATCC 13076 and 372 lux strains, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UPWr_S1, UPWr_S3, and UPWr_S4 phages are capable of infecting zoonotic pathogens such as S. Enteritidis as well as S. Gallinarum, which is the etiological factor of fowl typhoid. Regardless of their ability to infect various Salmonella serovars and lytic life cycle, they can be considered useful tools in the biological control of salmonellosis (Kuzmińska-Bajor et al, 2021). In this study, we found that UPWr_S1, UPWr_S3, and UPWr_S4 phages alone and the UPWr_S134 phage cocktail exhibited a great ability to decrease the number of Salmonella from biofilm structures in a 96-well microtiter plate and on stainless steel washers formed by strong and moderate biofilm producers, S. Enteritidis ATCC 13076 and 372 lux strains, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This has many implications for phage biology as well as for their practical applications. Although UPWr_S1, UPWr_S3, and UPWr_S4 phages showed similar biofilm removal properties in comparison to the UPWr_S134 phage cocktail and they exhibited a similar lytic profile (Kuzmińska-Bajor et al, 2021 ), for studies on the potential anti-biofilm application in a poultry watering system, the UPWr_S134 phage cocktail was applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsampling of the reads was performed with seqtk (Galaxy Version 1.3.2) (24). De novo assembly was conducted with the Shovill pipeline (Version 3.12.0) using default parameters (7). Assembly validation was performed in Galaxy BWA-MEM (24) and Blastn was used to identify similarities between the assembled genome and other genomic sequences.…”
Section: Sequencing and Genome Assemblymentioning
confidence: 99%
“…Using bacteriophages against food pathogens such as Salmonella to improve the food industry has received more attention. For that reason, most of the regulatory approvals are related to phage products of food pathogens (7).…”
Section: Introductionmentioning
confidence: 99%